Interpreting Leadership in Political Contests in Indonesia: Exploring Hamka’s Views - Anshori, Muhammad Helmi (Institut Agama Islam Negeri Kerinci, 2023)
The breeze of presidential elections has long been heard in Indonesian society, a year when political contests began to be heard everywhere. This is further compounded by the emergence of various forms of campaigns to seek support from the people. Departing from this, this writing explains the ideal concept of leadership in the current era from the perspective of Tafsir Al-Azhar. Because the impressions and views of this interpretation are highly suitable for the reality in which the Qur’an is interpreted. Regardless, we must understand the concept of leadership in the contemporary era, especially with the emergence of three major candidates for leadership in Indonesia. This article uses a descriptive analysis method that is expected to explain the concept of leadership in a profound, detailed, and ideal manner. The research results indicate that Tafsir al-Azhar provides a significant portion regarding leaders worthy of being chosen in the upcoming elections. The intended leader is one who fulfills his duties by promoting prosperity and well-being. This means how the leader carries out his tasks effectively based on the 1945 Constitution and Pancasila. Thus, a leader like this should be obeyed and followed. On the other hand, if the leader encourages the people to commit injustice and corruption, then they are not worthy of obedience, following, and compliance.